Akuntabilitas Pengelolaan Dana Desa terhadap Pemberdayaan dan Pembangunan Desa - Lola Indah Permata; Nur Fadjrih Asyik; Kurnia Kurnia (Jurnal Riset Akuntansi, 2026)
Accountability of Village Fund Management is one of the accountability forms that is done by the Village Government for their fund management that later will be shared openly with villagers and can be publicly accessed. The Accountability of the Prambangan Village Fund Management was not relevant; as there were differences in village fund details for the 2022-2023 budget year. Those differences occurred because obstacles appeared, i.e. the fund was late in distribution for the 2022 budget year. It affected the village's development and empowerment. Therefore, the role of the Village Government was crucially needed. Some efforts and role-taking were applied to overcome the burdens so that it would not happen again. Moreover, they were implemented to improve the accountability of Village Fund Management at the Prambangan Gresik, East Java. The study was qualitative. Furthermore, the data were primary which were taken from interview results. The instruments in the data collection technique were observation, interview, and documentation. As a result, it showed that the accountability of the Prambangan village fund management was not relevant and accountable, as there was a burden for the distribution fund for the 2022 budget year. Therefore, the Village Government made some efforts and roles together with the village apparatus and villagers to overcome the problems that happened.